Involvement of the extracellular matrix and integrin signalling proteins in skeletal muscle glucose uptake. (23rd September 2022) - Draicchio, Fulvia; Behrends, Volker; Tillin, Neale A.; Hurren, Nicholas M.; Sylow, Lykke; Mackenzie, Richard
Abstract: Whole‐body euglycaemia is partly maintained by two cellular processes that encourage glucose uptake in skeletal muscle, the insulin‐ and contraction‐stimulated pathways, with research suggesting convergence between these two processes. The normal structural integrity of the skeletal muscle requires an intact actin cytoskeleton as well as integrin‐associated proteins, and thus those structures are likely fundamental for effective glucose uptake in skeletal muscle. In contrast, excessive extracellular matrix (ECM) remodelling and integrin expression in skeletal muscle may contribute to insulin resistance owing to an increased physical barrier causing reduced nutrient and hormonal flux. This review explores the role of the ECM and the actin cytoskeleton in insulin‐ and contraction‐mediated glucose uptake in skeletal muscle. This is a clinically important area of research given that defects in the structural integrity of the ECM and integrin‐associated proteins may contribute to loss of muscle function and decreased glucose uptake in type 2 diabetes. Abstract : Abstract figure legend Nutrient and hormonal flux impeded by the accumulation of excessive extracellular matrix (ECM) proteins, causing a physical barrier for glucose uptake in skeletal muscle. Akt, protein kinase B; FAK, focal adhesion kinase; ILK, integrin‐linked kinase; IRS1, insulin receptor substrate 1; NCK2, non‐catalytic region of tyrosine kinase adaptor protein 2; PI3K, phosphatidylinositol 3‐kinase; PINCH, particularly interesting new cysteine–histidine‐rich protein; Rac1, Ras‐related C3 botulinum toxin substrate 1.